2013
DOI: 10.3174/ajnr.a3384
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Oligodendroglioma Genotypes Using Dynamic Susceptibility Contrast Perfusion-Weighted Imaging and Proton MR Spectroscopy

Abstract: BACKGROUND AND PURPOSE:Oligodendrogliomas with 1p/19q chromosome LOH are more sensitive to chemoradiation therapy than those with intact alleles. The usefulness of dynamic susceptibility contrast-PWI-guided 1 H-MRS in differentiating these 2 genotypes was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 40 publications
3
48
0
Order By: Relevance
“…Consistent with previous studies, we observed significant differences in diffusion MR measurements between 1p/19q co-deleted tumors from non-1p/19q co-deleted tumors [22][23][24][25] and IDH1 mutant from IDH1 wild-type diffuse gliomas [26]. Our findings did not appear to corroborate those of Tan et al [26], who reported a significantly higher rCBV in IDH WT compared with IDH MUT gliomas, though differences may stem from our smaller sample size as well as our more conservative statistical methods.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies, we observed significant differences in diffusion MR measurements between 1p/19q co-deleted tumors from non-1p/19q co-deleted tumors [22][23][24][25] and IDH1 mutant from IDH1 wild-type diffuse gliomas [26]. Our findings did not appear to corroborate those of Tan et al [26], who reported a significantly higher rCBV in IDH WT compared with IDH MUT gliomas, though differences may stem from our smaller sample size as well as our more conservative statistical methods.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have illustrated differences in diffusion and perfusion MR measurements between oligodendrogliomas from astrocytomas [20,21], 1p/19q co-deleted tumors (1p19q − ) from non-1p/19q co-deleted tumors (1p19q + ) [22][23][24][25], and IDH mutant (IDH MUT ) from IDH wild-type (IDH WT ) diffuse gliomas [26]. Presumably, these observed differences in diffusion MR measurements of apparent diffusion coefficient (ADC) and perfusion MR imaging measurements of relative cerebral blood volume (rCBV) between subtypes reflects known differences in tumor cell morphometry and aspects of vascular biology [27].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Provided that these techniques, particularly spectroscopy, continue to advance at their present rate, radiographic identification of 1p/19q status could be all that is necessary to categorize WHO grade II and III infiltrating gliomas by imaging. 18,[26][27][28][29] Our finding of an association between lower ADC values with 1p/19q codeletion has previously been described in small studies. 16,30 Further investigation will be necessary to define the optimal way of measuring ADC and to determine the physiologic correlate of ADC values in genetically defined oligodendroglioma.…”
Section: Discussionsupporting
confidence: 80%
“…[1,45] Kapoor confirmed that relative tumor blood volume (rTBV) was elevated only for low-grade gliomas with 1p19q co-deletion. This study also showed that tumors that were either 1p19q LOH or 1p LOH had higher rTBV and greater VEGF, CD31 and CD105 expression based on real-time PCR analyses compared with tumors that were 1p19q intact or 19q LOH.…”
Section: Image-guided Molecular Characterizationmentioning
confidence: 60%